2020
DOI: 10.1051/e3sconf/202022403025
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic textile materials with organosilicon impregnation

Abstract: In recent years, special attention has been paid to studying the properties of hydrophobic surfaces of textile materials. The authors provide an overview of the applied textile-processing chemicals and of the methods for imparting hydrophobic properties to textile materials. According to the analysis, it was found that waterand splash-proofing treatment occupies an important place in the finishing processes of textile materials, contributing to a change in their characteristics. The purpose of the research is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…An aqueous solution based on organosilicon compounds was used to hydrophobize textile products while maintaining their operational and hygienic characteristics. 5 Studies showed that it is impossible to obtain the same high hydrophobic effect on fabrics that were previously tinted using pigment technology as on fabrics that do not contain pigment. 6 This is due to the surface structure of the fabric.…”
mentioning
confidence: 99%
“…An aqueous solution based on organosilicon compounds was used to hydrophobize textile products while maintaining their operational and hygienic characteristics. 5 Studies showed that it is impossible to obtain the same high hydrophobic effect on fabrics that were previously tinted using pigment technology as on fabrics that do not contain pigment. 6 This is due to the surface structure of the fabric.…”
mentioning
confidence: 99%